Truth in Ficcion: Explicitism in Massive Serialized Collaborative Fictions - Zárate Guerrero, Felipe (Intuitio, 2025)
This paper examines the semantic challenges posed by Massive Serialized Collaborative Fictions (MSC fiction) to traditional theories of interpretation in fictional literature, focusing on the debate between intentionalism and explicitism. MSC fiction, characterised by its scale, episodic structure, and multiplicity of authors, complicates the intentionalist approach, which relies on discerning authorial intent to interpret fictional truths. Instead, the explicitist framework, emphasising intrinsic textual content and its connections across works, offers a more robust model for navigating the interconnected narratives of MSC fiction. The analysis begins with a definition of MSC fiction and its implications for interpreting fictional works, highlighting the limitations of intentionalism in addressing the complexities of serial and collaborative authorship. The paper further explores the role of retroactive continuity (retcon) in reshaping truths across interconnected fictional universes, challenging traditional notions of canonical authority. By investigating the concept of canonicity and proposing a hierarchy for resolving inconsistencies, the paper underscores the relevance of explicitism in maintaining narrative coherence across MSC fiction. Through case studies of iconic serial fiction, such as comic book universes and long-running literary sagas, the paper demonstrates how explicitism accommodates the dynamic nature of evolving fictional systems. By shifting the focus from authorial intent to the textual and intertextual dimensions of fiction, this approach provides a comprehensive framework for understanding the truths within MSC fiction. Ultimately, the study argues for the primacy of explicitism as a viable interpretive model for addressing the philosophical and semantic challenges posed by complex, collaborative narratives.